Integrating Mn-ZIF-67 on hollow spherical CdS photocatalysts forming a unique interfacial structure for the efficient photocatalytic hydrogen evolution and degradation under visible light. Issue 9 (27th August 2020) - You, Dan; Shi, Dajun; Cheng, Qingrong; Chen, Yanling; Pan, Zhiquan
Abstract : CdS@Mn-ZIF-67 heterojunction photocatalyst exhibited excellent photocatalytic activity for TC degradation and hydrogen evolution under visible light irradiation and are more effective than the single Mn-ZIF-67 or the hollow CdS nanospheres. Abstract : A series of novel hollow spherical composite photocatalysts was easily synthesized under mild conditions. First, by using SiO2 nanospheres as sacrificial templates, CdS hollow spheres with diameter of about 250 nm were obtained, with a thickness of about 18 nm. Then, Mn-ZIF-67 was coated on the surface of the hollow spherical CdS by magnetic stirring to obtain the hollow spherical CdS@Mn-ZIF-67 composite photocatalyst with large specific surface area (131.1 m 2 g −1 ) and very narrow pore size distribution (5.5 nm). The best result for hydrogen evolution was 4356 μmol in 4 h, which was nearly 74 times and 5 times higher than the single Mn-ZIF-67 and single CdS hollow nanospheres, respectively, and the H2 generation rate was 10889.2 μmol h −1 g −1 . The photocatalytic properties of four composite samples and three pure single materials on the degradation of tetracycline (TC) were studied, and the results showed that CdS@Mn-ZIF-67-1 achieved the best photocatalytic activity among them. The enhancement of the activity of the CdS@Mn-ZIF-67 photocatalysts is mainly attributed to the appropriate matching of the VB and CB of the two single components forming an effective channel for charge separation and transfer in the interfaces between CdS and Mn-ZIF-67. Moreover, a reasonable type II charge transfer mechanism was proposed based on the matched band structure of the single component, the active species trapping experiments, and the results of electron spin resonance (ESR).